The contemporary world - Claudio, Lisandro E.; Abinales, Patricio N. (Quezon City : C & E Publishing, Inc., 2018)
"This book will not take you on a country-per-country tour of the world. Instead, this book will focus on themes, problems, and issues. Central to the study of the contemporary world is the concept of globalization-the deepening global interconnectedness of places, ideas, economies, cultures and people."
Includes bibliography and index.
English text.
Keywords: Globalization